2021
DOI: 10.1101/2021.10.12.464044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A dual endosymbiosis drives nutritional adaptation to hematophagy in the invasive tick Hyalomma marginatum

Abstract: Many animals are dependent on microbial partners that provide essential nutrients lacking from their diet. Ticks, whose diet consists exclusively on vertebrate blood, rely on maternally inherited bacterial symbionts to supply B vitamins. While previously studied tick species consistently harbor a single lineage of those nutritional symbionts, we evidence here that the invasive tick Hyalomma marginatum harbors a unique dual-partner nutritional system between an ancestral symbiont, Francisella, and a more recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
1
0
0
Order By: Relevance
“…scapularis. This hypothesis is in accordance with a recent report of a dual endosymbiont dependency observed between Midichloria and Francisella symbionts in Hyalomma marginatum ticks driven by a nutritional adaptation [56]. It has also been shown that, although R. buchneri does possess the essential vitamin synthesis genes, some Ix.…”
Section: Discussionsupporting
confidence: 93%
“…scapularis. This hypothesis is in accordance with a recent report of a dual endosymbiont dependency observed between Midichloria and Francisella symbionts in Hyalomma marginatum ticks driven by a nutritional adaptation [56]. It has also been shown that, although R. buchneri does possess the essential vitamin synthesis genes, some Ix.…”
Section: Discussionsupporting
confidence: 93%